Redundancy Module Supply in Fuel Gas Compressor Header Pressure System: An Anti-Blackout Effort at Priok Power Generation Block Three - Pradana, Dwi Setyo; Wicaksono, Adam; Sukisworo, Mochamad Andrew (Journal of Mechanical Design and Testing, 2025)
System Pressure has a vital role to control the pressure of the header gas output from the fuel gas compressor which distributed to each Gas Turbine (GT) as the main supply of fuel for the operating needs of the gas turbine. On June 10, 2021, there was a disruption in the fuel gas compressor caused by a malfunction in the pressure system due to an abnormal voltage supply to the pressure transmitter which resulted in the Priok Power Generation block 3 experiencing a blackout. The purpose of this study is to prevent system failure by making modifications in the form of implementing redundancy power supply modules. The conclusion from the results of the modification shows that there has never been a recurrence of the incident since it was installed for the redundancy power supply modules of the pressure Fuel Gas Compressor (FGC) system. The implementation of the module can prevent blackouts, increase system reliability number 0.995, and effective mean time to failures (MTTF) of system 35,700,000 hours. The modification design using switch ensures continuous power without interruption.